Midlatitude Error Growth in Atmospheric GCMs: The Role of Eddy Growth Rate. Issue 23 (8th December 2021) - Sheshadri, Aditi; Borrus, Marshall; Yoder, Mark; Robinson, Thomas
Abstract: Several studies have established that atmospheric flows have a finite range of predictability, which may be reasonably considered a consequence of the underlying dynamics. In the midlatitudes, error growth is predominantly associated with baroclinic disturbances. We consider midlatitude error growth in two models: an idealized dry dynamical core and a comprehensive atmospheric general circulation model (GCM). By systematically varying equator to pole temperature gradients in the dynamical core, we show that with increasing Eady growth rates, the time elapsed before errors saturate decreases, shortening the window in which weather predictions may be useful. We also consider the limits of midlatitude predictability in the comprehensive moist GCM in a range of climates. Our results show that the times to error saturation are shorter in warmer climates than colder climates, suggesting that warmer climates are inherently less predictable. Plain Language Summary: It is well understood that weather predictions are only useful for a limited period. In the middle latitudes of the Earth, flows in the atmosphere are set by the effects of midlatitude storms. Understanding factors that set the limit up to which weather predictions are useful may help us improve our ability to provide accurate forecasts and prepare for changes in the period of useful weather prediction in different climates. We show in this work that the time scale over which eddies grow can change the time that models take to lose memory of initial conditions, thus changing the period over which weather predictions may be useful. Many realizations of a comprehensive atmospheric model run in a range of cold to warm conditions also reveal that midlatitude weather may be less predictable in warmer climates than colder climates. Key Points: Dynamical core model is overly predictable vis‐à‐vis the comprehensive model Reduced Eady growth rates are associated with a longer time to error saturation Midlatitude error growth in the comprehensive model is quicker in warmer climates and slower in cooler climates